Local Changes in Neurosteroid Levels in the Substantia Nigra Reticulata and the Ventral Tegmental Area Alter Chronic Ethanol Withdrawal Severity in Male Withdrawal Seizure‐Prone Mice. (20th December 2012) - Tanchuck, Michelle A.; Cozzoli, Debra K.; He, Ingrid; Kaufman, Katherine R.; Snelling, Christopher; Crabbe, John C.; Mark, Gregory P.; Finn, Deborah A.
<x xml:space="preserve">Abstract</x> Background Allopregnanolone (ALLO) is a potent positive modulator of γ‐aminobutyric acidA receptors (GABAARs) that affects ethanol (EtOH) withdrawal. Finasteride (FIN), a 5α‐reductase inhibitor that blocks the formation of ALLO and other GABAergic neurosteroids, alters EtOH sensitivity. Recently, we found that Withdrawal Seizure‐Prone mice from the first genetic replicate (WSP‐1) exhibited behavioral tolerance to the anticonvulsant effect of intrahippocampal ALLO during EtOH withdrawal and that intrahippocampal FIN significantly increased EtOH withdrawal severity. The purpose of this study was to determine whether neurosteroid manipulations in the substantia nigra reticulata (SNR) and ventral tegmental area (VTA) produced effects during EtOH withdrawal comparable to those seen with intrahippocampal ALLO and FIN. Methods Male WSP‐1 mice were surgically implanted with bilateral guide cannulae aimed at the SNR or VTA at 2 weeks prior to EtOH vapor or air exposure for 72 hours. Initial studies examined the anticonvulsant effect of a single ALLO infusion (0, 100, or 400 ng/side) at a time corresponding to peak withdrawal in the air‐ and EtOH‐exposed mice. Separate studies examined the effect of 4 FIN infusions (0 or 10 μg/side/d) during the development of physical dependence on the expression of EtOH withdrawal. Results ALLO infusion exerted a potent anticonvulsant effect in EtOH‐naïve mice, but a diminished anticonvulsant effect during EtOH withdrawal. Administration of FIN into the SNR exerted a delayed proconvulsant effect in EtOH‐naïve mice, whereas infusion into the VTA increased EtOH withdrawal duration. Conclusions Activation of local GABAARs in the SNR and VTA via ALLO infusion is sufficient to exert an anticonvulsant effect in naïve mice and to produce behavioral tolerance to the anticonvulsant effect of ALLO infusion during EtOH withdrawal. Thus, EtOH withdrawal reduced sensitivity of GABAARs to GABAergic neurosteroids in 2 neuroanatomical substrates within the basal ganglia in WSP‐1 male mice.